3D modeling and experimental investigation for tool deflection in end mill cutting of AISI 1045. (2021) - Thakur, Ankit; Singh, Gurmeet; Minhas, Navdeep; Sharma, Varun; Bansal, Anuj
Abstract: The present paper investigates the tool deflection in three dimensions for two different tool diameters during end milling operation and validates the experimental findings with the finite element results. Cutting forces (i.e., radial cutting force, tangential cutting force, axial cutting force) exerted by the tool on AISI 1045 steel substrate under different combinations of cutting parameters (viz. feed rate, cutting speed and depth of cut) were measured using a dynamometer. For more accurate prediction of tool deflection using finite element analysis (FEA), the tool-workpiece contact region was sliced into small segments for the equal distribution of cutting forces. In order to verify the experimentally measured inaccuracy in the cut profile using a coordinate measuring machine (CMM) under different sets of parameters, the experimental results were compared with the predicted values of FEA. From the results, it was observed that the cutting forces were comparatively larger in magnitude for the larger tool diameter. Also, the depth of cut was found to be the most influential parameter among all, whereas the effect of feed rate and cutting speed on profile error was found to be insignificant. Further, the results show good agreement between the predicted FEA simulated tool defection and experimental values.